KEDUDUKAN HUKUM ADAT DALAM HUKUM ISLAM - Abd. Rauf (IAIN Ambon, 2017)
The custom of urf shahih, either in the am form (general) or in the typical form (special) can be used as an argument in the Islamic law. Islamic criminal law as qishas, was not a new law but the long-standing (custom) in Arab community. The primary changes made by Islamic law in the qishas is included the balance principle into a qishas legal framework. Similarly, in the commercial transactions, for example, the role of custom is seen at bai'a-ariyah institutions, tax payments in the form of usyur (1/10), the use of scale, and sizes, as well as divorce. Therefore there is relationship between customary law and Islamic law. In dealing with the custom of Arab community, Islamic law take the ways, among others: (1) Islamic law adopted the custom as a whole, either in principle aspects or in the implementation aspects, for example, diat, ariyah sale and purchase, (2) Islamic law adopt the customs from the principle aspects, but in practice adapted to Islamic law. For example, in the case of ila' and zihar has been prevailed in the custom of pre-Islamic Arab, and (3) Islamic law make nasakh or abrogated the custom and the old institutions, either in principle or in the implementation terms. Keywords : customary law , relations , Islamic law